Macrophages directly contribute collagen to scar formation during zebrafish heart regeneration and mouse heart repair - Simões, Filipa C.; Cahill, Thomas J.; Kenyon, Amy; Gavriouchkina, Daria; Vieira, Joaquim M.; Sun, Xin; Pezzolla, Daniela; Ravaud, Christophe; Masmanian, Eva; Weinberger, Michael; Mayes, Sarah; Lemieux, Madeleine E.; et al. (Nature communications, 2020)
Canonical roles for macrophages in mediating the fibrotic response after a heart attack include extracellular matrix turnover and activation of cardiac fibroblasts to initiate collagen deposition. Here we reveal that macrophages directly contribute collagen to the forming post-injury scar. Unbiased transcriptomics shows an upregulation of collagens in both zebrafish and mouse macrophages following heart injury. Adoptive transfer of macrophages, from either collagen-tagged zebrafish or adult mouse GFP tpz -collagen donors, enhances scar formation via cell autonomous production of collagen. In zebrafish, the majority of tagged collagen localises proximal to the injury, within the overlying epicardial region, suggesting a possible distinction between macrophage-deposited collagen and that predominantly laid-down by myofibroblasts. Macrophage-specific targeting of col4a3bpa and cognate col4a1 in zebrafish significantly reduces scarring in cryoinjured hosts. Our findings contrast with the current model of scarring, whereby collagen deposition is exclusively attributed to myofibroblasts, and implicate macrophages as direct contributors to fibrosis during heart repair. Macrophages mediate the fibrotic response after a heart attack by extracellular matrix turnover and cardiac fibroblasts activation. Here the authors identify an evolutionarily-conserved function of macrophages that contributes directly to the forming post-injury scar through cell-autonomous deposition of collagen.